Dispersion of graphene oxide and its application prospect in cement-based materials: a review. Issue 3 (1st March 2023) - Wang, Huangqi; Zhang, Liran; Wang, Dongmin; Geng, Danhua; Zhang, Ming; Du, Wenqian; Chen, Huixin
Abstract: Graphene oxide (GO) is a novel nano-carbon material with excellent mechanical properties. It can be used in cement-based materials to induce cement hydration and enhance the strength and the toughness of cement-based material. However, during the practical application, due to high calcium ion concentration and the highly alkaline environment of the cement pore solution, GO has a serious agglomeration problem, which does not improve hydration and cement paste mechanical properties. Therefore, three typical structural models of GO are initially discussed in this article followed by a summary of the primary GO modification methods. Finally, prospects of GO modification strategies, classified based on local structures, are put forward for GO-cement composites. Graphical Abstract: UF0001